Case Report Pemberian Psikoedukasi Kepada Keluarga Yang Merawat Orang Dengan Gangguan Jiwa Di Desa Banteran - Dewanti, Win Asmo (PENA NURSING, 2024)
Background : Mental disorders are disturbances in thought processes, emotions, behavior and perception due to disturbances in the brain. The presence of mental dysfunction can disrupt an individual's social relationships with other people and can trigger stress for the individual's family members. Thus, family support in the form of care for family members who suffer from mental disorders must be optimal. The family as caregivers plays an important role in accompanying people with mental disorders in living their daily lives. Family support is very necessary for the success of the recovery process for people with mental disorders. However, it is known that the role played by the family is still not optimal, so psychoeducation is needed. Purpose: Increase family knowledge about the concept of mental disorders and how to care for family members with mental disorders in everyday life. Methods: Case report applying the implementation of evidence based practice in nursing care. Results: After implementing psychoeducational intervention to families caring for people with mental disorders for three sessions, the results showed that there was an increase in family knowledge regarding how to care for family members who experience mental disorders. Conclusion: Psychoeducation is one of the interventions that must be given to families caring for ODGJ because family support is very necessary for the success of the recovery process for people with mental disorders.Keywords: People with mental disorders (ODGJ), family,  psychoeducation.